All-optical control of long-lived nuclear spins in rare-earth doped nanoparticles - D. Serrano (Nature Portfolio, 2018)
The long coherence time of rare-earth dopant spins in bulk crystals has made them attractive qubit candidates but creating nanoscale devices often introduce decoherence sources that reduce performance. Serrano et al. demonstrate all-optical control of rare earth doped nanoparticles with millisecond coherence times.